Enhanced Lubrication Ability of Polyalphaolefin and Polypropylene Glycol by COOH-Functionalized Multiwalled Carbon Nanotubes as an Additive - Kumar H.; Harsha A.P. (My University, 2025)
In the current study, the tribological performance of two different synthetic lubricants, i.e., polyalphaolefin (PAO 100) and polypropylene glycol (PPG 2000), were analyzed. The COOH-functionalized multiwalled carbon nanotubes (MWCNTs) were used as an additive in varying fractions (0.025-0.15 wt.%). The friction and wear studies were carried out as per ASTM D6425 by using SRV 5 tribometer with a ‘ball on disk’ configuration. The results showed that tribological performance gets enhanced remarkably with the inclusion of MWCNTs in both lubricants as compared to the pure lubricants. PAO 100 demonstrated the lowest coefficient of friction and wear volume at a concentration of 0.025 and 0.05 wt.% of MWCNTs, respectively. However, 0.025 wt.% of additive in PPG 2000 exhibited the maximum reduction in the coefficient of friction (~6%) and wear volume (~86%). The results confirmed that PAO 100 showed better tribological performance as compared to PPG 2000. The lubrication mechanism of MWCNTs has been demonstrated through the investigation of worn steel ball surfaces by using various characterization techniques such as scanning electron microscope, energy-dispersive x-ray spectroscopy (EDS) and scan probe microscope. © 2021, ASM International.